More Health Hazards Are Expected if Melamine Wastes Are Allowed to Be Used as Fertilizers - Leung, Ping-Chung; Bik-San Lau, Clara; Cheng, Sau-Wan; Lam, Hon-Ming (Current Nutrition & Food Science, 2014)
The adulteration of milk with melamine in China in 2008 caused worldwide alarm over the use of unwanted chemicals in food. The melamine waste polluted the soil and this further resulted in health hazards. This study investigated the hazards of melamine wastes which are used as fertilizers. A cultivation experiment was designed to determine the contents of melamine in the plants and soil where melamine had been used as a fertilizer. The results showed that melamine detected in the first round of the harvested plants was 22.3 ± 4.8 ppm and that in the second round of the harvested plants it was 41.1 ± 16.7 ppm. In both of these situations the U.S.A.’s Food and Drug Administration’s (FDA) limit was exceeded. The soil residue contained a very high concentration of melamine, reaching a level of 235.1 ± 91.3 ppm. Melamine functions as a good fertilizer, comparable to urea. However, the plants absorbed the melamine, and the melamine content was higher than the level which is recommended as acceptable by the FDA. Our study supported the legitimate concern about melamine contamination in crops where melamine wastes have been used as a fertilizer. The toxic material remaining in the soil was a major concern.
Keywords: melamine